2021
DOI: 10.3389/fcimb.2021.784279
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Investigations of Potential Protein Biomarkers in Sera of Rabbits Infected With Schistosoma japonicum

Abstract: Schistosomiasis is a chronic parasitic disease that continues to be a pressing public health problem in many developing countries. The primary pathological damage from the disease is granuloma and fibrosis caused by egg aggregation, and early treatment can effectively prevent the occurrence of liver fibrosis. Therefore, it is very important to identify biomarkers that can be used for early diagnosis of Schistosoma japonicum infection. In this study, a label-free proteomics method was performed to observe the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…S. japonicum eggs were isolated from the livers of infected New Zealand rabbits as described previously. 23 …”
Section: Methodsmentioning
confidence: 99%
“…S. japonicum eggs were isolated from the livers of infected New Zealand rabbits as described previously. 23 …”
Section: Methodsmentioning
confidence: 99%
“…The most commonly investigated samples are plasma/serum and plasma/serum-derived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70]. Importantly, a number of studies identified parasite proteins within the host's systemic or vesicular proteome, supporting the relevance of host proteomics also in revealing novel diagnostic markers [67,68,71,72,74,75].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
“…Such analysis could however be particularly useful in revealing novel facets of the pathological mechanisms associated with human strongyloidiasis, especially when applied in comparative studies. Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, analysis of the serum proteome in the context of schistosomiasis could provide the basis to comprehend the metabolic reprogramming operating at target tissues. Recent studies have investigated the serum proteome during S. japonicum infection in animal models of the disease and markers of infection have been proposed ( 12 , 13 ). To our knowledge, we are the first to investigate the serum proteome in the context of S. mansoni infection, in the murine model, with a particular focus on proteins related to lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%